Outcomes of operatively treated calcaneal tuberosity avulsion fractures. Issue 3 (March 2022) - Hong, Choon Chiet; Lim, Joel Xue Yi; Tan, Jun Hao; Pearce, Christopher Jon
Abstract: Background: Calcaneal tuberosity avulsion fractures are uncommon but when present should be treated emergently due to the high risk of skin compromise. Multiple fixation techniques have been reported in the literature but there are little data regarding the ideal fixation construct and outcomes. We aimed to characterize the clinical presentation, focussing on soft tissue compromise and outcomes of operatively treated calcaneal tuberosity avulsion fractures with its associated complications. Methods: A retrospective review of all surgically treated calcaneus fracture in our institution from Jun 2008 to Jun 2017 was done. We reviewed patients' demographics, types of avulsion fracture, presence of preoperative skin compromise, age of fracture, time to operation, types of fixation construct, postoperative weight bearing regime, union rates, complications and revision surgeries if present. Results: We found 9 patients from our database who met the inclusion criteria. They had an average age of 55.6 (range: 43 - 90) years with 5 (55.6%) of them aged 60 years and older. Seven (77.8%) patients were female. Four out of 9 patients (44.4%) presented with soft tissue compromise (3 cases of skin tenting and 1 case of blistering). None of them required soft tissue reconstructive surgery for skin defects postoperatively. However, 2 patients (22.2%) had wound complications after surgery requiring prolonged wound care for up to 4 months. There were 2 patients with fixation failure whereby both were allowed weight bearing prematurely. All of them were able to ambulate independently at their last review. Conclusion: Calcaneal tuberosity avulsion fractures have a high prevalence of soft tissue compromise and warrant early attention. This condition should be treated as both a bony and soft tissue injury rather than just a bony fracture alone. Management of this injury should take into account fracture reduction and stable fixation with neutralization of the Achilles tendon forces.